POLA PENGELOLAAN ARSIP DIGITAL DALAM MENDUKUNG KEMAMPUAN ORGANISASI DI DPUPRPKP KOTA MALANG - Laily Khoiri Syafiya; Sokhibul Ansor; Adi Prasetyawan (Departemen Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2024)
The development of advanced information technology can make it easier for every agency to manage important documents. Archives are one of the important documents that must be managed by archivists, which will later be used as accountability materials. The development of information technology has given rise to various archival systems. Archives that are stored electronically can make it easier for archive users to fulfil their information needs. The method used in this research is a qualitative research method with data collection techniques using observation, interviews, and documentation techniques obtained from informants involved in digital archive management activities carried out by DPUPRPKP Malang City. The existence of electronic archives can affect the effectiveness of organisations in carrying out archive management, archive maintenance, and archive shrinkage. The theory used in this research is the record continuum. The record continuum theory is a model of archive management with control through the system from the time the archive is created until the archive can be accessed by the public. The purpose of this research is to describe the digital archive pattern in supporting organisational effectiveness at DPUPRPKP Malang City and describe the obstacles found in the digital archive management pattern in supporting organisational effectiveness at DPUPRPKP Malang City.